2020
DOI: 10.1108/ijchm-07-2019-0605
|View full text |Cite
|
Sign up to set email alerts
|

How live chat assistants drive travel consumers’ attitudes, trust and purchase intentions

Abstract: Purpose By adopting a social presence theory perspective, this study aims investigate the influence of perceived usefulness of live chat services and of their unique human attributes on customer attitudes, beliefs and behaviours in the context of online travel shopping. Design/methodology/approach Based on a cross-sectional survey research involving 8 travel provider websites and 631 travel consumers, this work applies structural equation modelling to analyse the data. Findings The results illustrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 70 publications
3
71
0
4
Order By: Relevance
“…However, limitations in using such theories in their singularity have been made apparent, bringing about a second stream of literature examining VA adoption through PSR theories (Ki et al, 2020); this literature suggests that VA adoption is not only based on willingness to adopt technology but also due to the relationships built between consumers and voice‐based (or “human‐like”) systems (e.g., Schweitzer et al, 2019). Another substream of HCI literature has examined the negative role of privacy concerns, and has been seen to be discussed in both main streams of research (e.g., McLean et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…However, limitations in using such theories in their singularity have been made apparent, bringing about a second stream of literature examining VA adoption through PSR theories (Ki et al, 2020); this literature suggests that VA adoption is not only based on willingness to adopt technology but also due to the relationships built between consumers and voice‐based (or “human‐like”) systems (e.g., Schweitzer et al, 2019). Another substream of HCI literature has examined the negative role of privacy concerns, and has been seen to be discussed in both main streams of research (e.g., McLean et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Originally derived from the SRT, social presence is shown to affect users' attitudes (Hassanein & Head, 2007), loyalty (Cyr et al, 2007), online behaviors (Chung et al, 2015; Ogara et al, 2014), and trust building (Gefen & Straub, 2003, 2004; Lu et al, 2016; Ogonowski et al, 2014). Specifically, studies have demonstrated that technologies conveying a greater sense of social presence, such as live chat services (McLean et al, 2020), can enhance consumer trust and subsequent behavior (Hassanein et al, 2009; Lu et al, 2016; Mackey & Freyberg, 2010; Ye et al, 2019).…”
Section: Conceptual Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Broadly, purchase intention is defined as one's resolve to buy a particular product or service (Dodds et al, 1991). Although the gap between actual behavior and behavioral intention has been acknowledged (Ajzen and Fishbein, 1980), hospitality research recognized the critical role of purchase intention for overall service business success (Kang et al, 2018;McLean et al, 2020). Furthermore, competitive advantage and customer purchase intention have been aligned with consumer perceptions of the brand (Donnelly et al, 2020).…”
Section: Purchase Intentionmentioning
confidence: 99%